Avaliação do uso de trincheiras de infiltração para atenuação de picos de cheia utilizando o SWMM - Feitosa, Francisco Fábio de Sousa (2015)
The growth of urban centers and the process of urbanization in recent decades worldwide have caused many impacts on the environment, especially the water cycle, bringing with it an increase in the number and magnitude of urban flooding. This study aimed to assess the process of urbanization of an area of Crato-CE municipality, analyzing the generated runoff and proposing a solution for its reduction through the use of infiltration trenches, deployed on the promenade, getting only water from the roofs of the lots. Was used for the simulations the computer program Storm Water Management Model - SWMM with parameters taken from the literature. Two scenarios were studied, the first simulated the entire study area, urbanized in its extreme situation. In the second scenario, the trenches were included in the previous model and analyzed the results. Simulations have shown that the place by total urbanization can cause problems with the runoff and the proposed solution by using infiltration trenches is demonstrated effective in reducing peak flows, showing in most cases able to reduce at least 70% of the flow generated by batches. Analyzing the area as a whole we are not observed delays of peaks due to the influence of the flow generated by the streets, occurring in all cases after 12 minutes by precipitation. Stands out, finally, that through the use of drainage practices Low Impact Development (LID) the benefits go far beyond addressing the problems of flooding in the installation area, and may also reduce them in other areas downstream and favor the increase in water site underground resources reserves